Submarine Optical Fiber Sensing System for the Real-Time Monitoring of Depth, Vibration, and Temperature - Liu, Zhengyong; Zhang, Shengqi; Yang, Chengkun; Chung, Weng-Hong; Li, Zhaohui (Frontiers in Marine Science, 2022)
Ocean observation becomes increasingly important as the ocean climate changes diversely and the marine disasters (such as tsunamis, typhoon, and earthquakes) occur frequently, which typically requires widespread and reliable monitoring techniques. In such a scenario, this paper presents a submarine optical fiber sensing system to realize real-time monitoring of the environmental parameters. The system consists of an undersea optical interrogation module together with multiple fiber Bragg grating (FBG)-based sensors, particularly for the measurement of depth, vibration, and temperature. The experimentally demonstrated sensitivities of the pressure, temperature, and vibration sensors are -1.993 nm/MPa, 0.08 nm/°C, and 0.139 nm/g (g = 9.8 m/s2), corresponding to the resolutions of 0.25 kPa, 0.006°C, and 0.004 g, respectively, based on the interrogation resolution of 0.5 pm. To verify the feasibility and reliability of the proposed submarine sensing system, a prototype was developed and a proof test under the sea was conducted in an area close to Pearl River Estuary in China. The achieved results from the sea test show promising accuracy that is comparable to the commercially available electric-based sensors. Good characteristics of the surface water wave were observed by conducting the fast Fourier transform of the measured depth change, which shows a dominant frequency of 0.25 Hz. The system provides the flexibility of replacing various optical fiber sensors easily and the capability of real-time monitoring in a remote way. The demonstrated submarine sensing system could find potential applications in real-time monitoring of the undersea ecosystem and the environmental evolution where multiparameter sensing is in demand.